(untitled) (East West Medical College Journal, 2026)
Introduction: Pancreatitis is a global health problem. Up to 10-25% of patients who have no clear risk factors and are classified as idiopathic chronic pancreatitis (ICP). The pathogenesis of ICP is poorly understood. During last two decades it has become acceptable that development of pancreatitis requires a combination of genetic, environmental, structural or toxic insult. The aim of the study was to observe the mutation in PRSS1 gene in pediatric patients with pancreatitis. Methods: It was a cross-sectional descriptive study performed at the department of Paediatric Gastroenterology and Nutrition, BSMMU, Dhaka, Bangladesh from May 2019 to October 2020. Results: Out of 18 paediatric patients with pancreatitis 12, (66.7%) were female and six (33.3%) males. The mean age of the patients was 12.1 (±3.3) years and the mean age at first presentation was 8.7 year. Abdominal pain (100%) was the most common presenting feature. In the current study, in three (17%) patients PRSS1 gene mutation were observed while in most (15, 83%) of the cases such mutations were absent. In our study, a missense mutation G>A, was found that causes alteration of amino acid from Histidine to Arginine at 122 codon of PRSS1 gene and this mutation was pathogenic. There was one (33.3%) patient each with pancreatic duct dilatation, biliary sludge and pancreatic calcification had PRSS1 mutation. On etiological distribution, idiopathic and biliary tract abnormality showed statistical significance (p<0.05). Conclusion: In the current study, out of 18 pancreatic patients PRSS1 gene mutation was observed in three (17%) patients. These three patients with PRSS1 genetic mutation had pancreatic duct dilatation, biliary sludge and pancreatic calcification respectively. EWMCJ Vol. 14, No. 1, January 2026: 4-16